BATHARA KATONG, REYOG PONOROGO, DAN PENYEBARAN ISLAM DI JAWA - Uswatun Hasanah (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
The purpose of this article is to describe the origin of the town ofPonorogo as well as the existence of Reyog Ponorogo as local wisdomthat has been known worldwide. Historical emergence and establishmentof Reyog Ponorogo and the town of Ponorogo, relating to the role of thethe first head of this district, namely Bathara Katong, which brings withit the mission of spreading Islam. Results of the analysis of this articleproves that through Reyog Ponorogo, Bathara Katong open the gates ofIslam in Ponorogo.